Laying ethical foundations for clinical research - Jon Harkness; Susan E. Lederer; Daniel Wikler (Bulletin of the World Health Organization)
This section looks back to some ground-breaking contributions to public health, reproducing them in their original form and adding a commentary on their significance from a modern-day perspective. Jon Harkness, Susan Lederer and Daniel Wikler review the 1966 paper by Henry K. Beecher on ethics and clinical research. The original article is reproduced from The New England Journal of Medicine by permission of the Massachusetts Medical Society.